2021
DOI: 10.1108/caer-06-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

Does digital inclusive finance promote agricultural production for rural households in China? Research based on the Chinese family database (CFD)

Abstract: PurposeThe development of digital inclusive finance appears to be able to solve the difficulty of traditional finance, which cannot completely cover agriculture and farmers and provides better financial services and products to Chinese farmers. Thus, it improves the farmers' enthusiasm for agricultural production. The purpose of this paper is to clarify whether this goal is indeed being achieved.Design/methodology/approachThis paper theoretically analyzes the mechanism that influences the effect of digital inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…We find that digital finance is more beneficial for older and uneducated rural households to escape poverty. Furthermore, our results further enrich the relevant literature on the inclusive finance and functions of digital finance [ 2 , 17 , 22 , 28 ].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…We find that digital finance is more beneficial for older and uneducated rural households to escape poverty. Furthermore, our results further enrich the relevant literature on the inclusive finance and functions of digital finance [ 2 , 17 , 22 , 28 ].…”
Section: Introductionsupporting
confidence: 77%
“…China’s digital finance is mainly mobile payments, online loans, digital insurance and online investments [ 25 – 27 ]. With the spread of the Internet and smartphones, digital finance in China has made great strides, which has greatly increased the accessibility and convenience of formal financial services, especially for those who previously did not have access to them [ 28 – 30 ]. However, since research on the impact of digital finance on poverty reduction is still very limited, we try to explore the role of digital finance in China’s rural poverty reduction, as China is the most widely used country for digital finance in the world.…”
Section: Introductionmentioning
confidence: 99%
“…One reason might be rural households' differing experiences of participating in financial inclusion. Research has shown that farmers who have experienced financial inclusion are more likely to use such services again [27,[72][73][74]. Farmers' experience with inclusive finance can expand digital financial widening and deepening, which in turn increases the effect of digital financial inclusion.…”
Section: Further Discussionmentioning
confidence: 99%
“…The PKU-IFDI includes sub-indexes for financial inclusion widening, financial inclusion deepening, and financial inclusion digitalization, which are the mechanisms in our theoretical framework. Studies have described the calculation methodology and scientific nature of this index [72][73][74]. To illustrate the representativeness of the data, firstly we showed the correlation between prefecture-level PKU-IFDI and prefecture-level GDP in 2018 in Figure 3, where we found a significant positive relationship between the two (0.82).…”
Section: Independent Variable On Digital Financial Inclusionmentioning
confidence: 90%
“…A product's Internet determines the satisfaction level of a customer (Zhou, Liu, & Liu, 2021). Internet is something that commercial banks can never overlook (Ujunwa, Ujunwa, Onah, & Ogundele, 2021).…”
Section: Wwwpsychologyandeducationnetmentioning
confidence: 99%